NUMERICAL INVESTIGATION OF HEAT TRANSFER UNDER IMPINGING ANNULAR JETS - Pal, Tarun Kanti; Chattopadhyay, Himadri; Mandal, Dipak Kumar; Bhattacharyya, Suvanjan (MATTER: International Journal of Science and Technology, 2016)
In the present work, numerical investigations have been done to predict the transport phenomena and heat transfer characteristics of laminar annular jets impinging on a surface. For analysis purpose, the characteristics of an annular jet has been compared with that of a circular jet at the same Reynolds number with same amount of mass and momentum efflux at the nozzle exit. The Reynolds number of the jet is defined on the basis of width of the annular part. The distribution pattern of the Nusselt number over the impinging surface scales with Re0.54.